Responses of Winter Wheat Yields to Warming-Mediated Vernalization Variations Across Temperate Europe - Wu, Xiuchen; Liu, Hongyan; Li, Xiaoyan; Tian, Yuhong; Mahecha, Miguel D. (Frontiers in Ecology and Evolution, 2017)
Rapid climate warming, with much higher warming rates in winter and spring, could affect the vernalization fulfillment, a critical process for induction of crop reproductive growth and consequent grain filling in temperate winter crops. However, regional observational evidence of the effects of historical warming-mediated vernalization variations on temperate winter crop yields is lacking. Here, we statistically quantified the interannual sensitivity of winter wheat yields to vernalization degree days (VDD) during 1975–2009 and its spatial relationship with multi-year mean VDD over temperate Europe (TE), using EUROSTAT crop yield statistics, observed and simulated crop phenology data and gridded daily climate data. Our results revealed a pervasively positive interannual sensitivity of winter wheat yields to variations in VDD (γVDD) over TE, with a mean γVDD of 2.8 ± 1.5 kg ha–1 VDD–1. We revealed a significant (p < 0.05) negative exponential relationship between γVDD and multi-year mean VDD for winter wheat across TE, with higher γVDD in winter wheat planting areas with lower multi-year mean VDD. Our findings shed light on potential vulnerability of winter wheat yields to warming-mediated vernalization variations over TE, particularly considering a likely future warmer climate.